Chemical reaction effects on MHD flow past a linearly accelerated vertical plate with variable temperature and mass diffusion in the presence of thermal radiation - Muthucumaraswamy, Rajamanickam; Geetha, E. (Zielona Góra: Uniwersytet Zielonogórski)
An exact solution of first order chemical reaction effects on a radiative flow past a linearly accelerated infinite isothermal vertical plate with variable mass diffusion, under the action of a transversely applied magnetic field has been presented. The plate temperature is raised linearly with time and the concentration level near the plate is also raised to C`w linearly with time. The dimensionless governing equations are tackled using the Laplace-transform technique. The velocity, temperature and concentration fields are studied for different physical parameters such as the magnetic field parameter, radiation parameter, chemical reaction parameter, thermal Grashof number, mass Grashof number, Schmidt number, Prandtl number and time. It is observed that velocity increases with decreasing magnetic field parameter or radiation parameter. But the trend is just reversed with respect to the chemical reaction parameter.
Keywords: accelerated; isothermal; radiation; vertical plate; heat transfer; mass transfer; magnetic field; chemical reaction